Circuit Implementation and Antisynchronization of an Improved Lorenz Chaotic System - Li Xiong; Yan-Jun Lu; Qi-Meng Zhang; Zhi-Yu Zhang (Shock and Vibration)
An improved Lorenz chaotic system is proposed, making it into a circuit which is easy to be implemented by using some basic electronic components. The antisynchronization error systems can be asymptotically stabilized at the origin with three different methods which are proposed to control the improved Lorenz system. Theoretical analyses and simulation results are given to demonstrate the feasibility and effectiveness of these proposed schemes. Then the hardware circuit for the proposed Lorenz system is implemented by repeated optimization design. Experimental results show that the circuit has good comprehensive performance.